Inverse sum indeg coindex of graphs - Pattabiraman, K. (Carpathian Mathematical Publications, 2019)
The inverse sum indeg coindex ISI(G) of a simple connected graph G is defined as the sum of the terms d_G(u)d_G(v)d_G(u)+d_G(v) over all edges uv not in G, where d_G(u) denotes the degree of a vertex u of G. In this paper, we present the upper bounds on inverse sum indeg coindex of edge corona product graph and Mycielskian graph. In addition, we obtain the exact value of both inverse sum indeg index and its coindex of a double graph.